Pengaruh Ragam Produk dan Kualitas Produk Terhadap Keputusan Pembelian : (Studi Kasus Pada Umkm Telur Asin Kencana Desa Wanasari Brebes) - Ardhan Adiyatma Raharjo; Nur Afridah; Indah Dewi Mulyani (Journal of Management and Creative Business, 2024)
This study aims to determine and analyze how much influence the variety of products and product quality has on purchasing decisions at UMKM Kencana Salted Eggs Wanasari Brebes. The approach used in this research is a quantitative approach. The sampling technique in this study was Nonprobability sampling, with the sampling method used being Incidental sampling. With the number of samples used as many as 100 respondents. The results in this study show: (1) product variety has a positive and significant effect on purchasing decisions. This is based on the tcount value of 12.044 and the t table of 1.985 or 12.044> 1.985 with a significance value of 0.000 <0.05. (2) product quality has a positive and significant effect on purchasing decisions. This is based on the tcount value of 2.641 and the ttable of 1.985 or 2.641> 1.985 with a significance value of 0.010 <0.05. (3) simultaneously the variable product variety and product quality have an effect on purchasing decisions. This is supported by the value of Fhitung> Ftabel, namely 1138.470> 3.089 with a significance value of 0.000 <0.05 and a coefficient of determination (R Square) of 0.959. From this figure it means that product variety and product quality affect purchasing decisions by 95.9%. Meanwhile, the remaining 4.1% is influenced by other variables not included in the study.